Sharing of health services in the Caribbean : current utilization patterns and possible options - Lalta, Stanley ([s.n.] [S.l.], 1995)
Looks at the regional experience with sharing secondary and tertiary care services and the possibilities for enhancing its role as an integral part of the health strategies in Member States.